La gestión del talento humano y el desempeño laboral de los trabajadores del Camal Municipal de Riobamba. - Maigua Guaranga, Ivonne Yadira (2023)
Managing human talent is necessary for all organizations because it encompasses strategies for hiring, training, motivating, and developing employees. Influencing their performance when carrying out their activities efficiently, for which it is essential to know the relationship between the management of the human talent of the Riobamba Municipal Slaughterhouse with its workers. For this reason, research was carried out based on analyzing the perception of workers under the management of human talent to detect positive or negative influences on their performance. Through the application of the survey instrument, the results were determined and analyzed with descriptive statistics and the SPSS V.27 software. The results are that the management of human talent affects workers' work performance since there are factors that are found to have shortcomings and need improvement processes, such as motivation, remuneration, and communication. The null and affirmative hypotheses were verified using the Chi-Square and hypothesis testing, demonstrating a significant relationship between human talent management and job performance. They concluded that it was not in optimal condition and ended with a proposal Human talent management model.